DC - DC converters for future renewable energy systems - Priyadarshi, Neeraj; Bhoi, Akash Kumar; Bansal, Ramesh C.; Kalam, Akhtar (Springer, 2022)
The book presents the analysis and control of numerous DC-DC converters widely used in several applications such as standalone, grid integration, and motor drives-based renewable energy systems. The book provides extensive simulation and practical analysis of recent and advanced DC-DC power converter topologies. This self-contained book contributes to DC-DC converters design, control techniques, and industrial as well as domestic applications of renewable energy systems. This volume will be useful for undergraduate/postgraduate students, energy planners, designers, system analysis, and system governors
Design and Control of DC-DC Converters in a PV based LVDC Microgrid.- High Gain Buck-Boost Converter for Solar Photovoltaic (PV) System.- Developed Boost Converter With Generalized Quadratic Boosting Cell To Minimize Capacitor Voltage Stresses And Reduce The Cost Of Utilized Capacitors.- Comparative Analysis of Nonlinear SMC Controller with Linear PID Controller for Flyback Converter.- Effect of Irradiance on THD of Neutral Point Clamped Inverter Fed from Pv Cell.- Bidirectional Interleaved Switched Capacitor Dc-Dc Converter for Renewable Energy Applications.- LUO Converters for Renewable Energy Applications.
Keywords: Electronic circuits; Electronics; Microelectronics; Energy systems; Engineering; Hardcover, Softcover / Technik/Elektronik, Elektrotechnik, Nachrichtentechnik; Aufsatzsammlung